2003
DOI: 10.1046/j.1360-0443.2003.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Marginality among older injectors in today's illicit drug culture: assessing the impact of ageing

Abstract: Our respondents' experiences draw attention to the need to refine the field's theoretical and practical understandings of what it means to be marginal and its consequences for older drug users and people in general. The results also point to what happens when society changes but some of its members do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 31 publications
4
63
0
2
Order By: Relevance
“…Previous studies on HIV concerns for injection drug users over the age of 50 have been funded by the National Institute on Aging and the National Institute on Drug Abuse (Anderson & Levy, 2003;Auberbach, 2003). SAMHSA studies (2002) that examined drug use in people over the age of 50 identified the relationship between aging, drug use, and future treatment needs.…”
mentioning
confidence: 99%
“…Previous studies on HIV concerns for injection drug users over the age of 50 have been funded by the National Institute on Aging and the National Institute on Drug Abuse (Anderson & Levy, 2003;Auberbach, 2003). SAMHSA studies (2002) that examined drug use in people over the age of 50 identified the relationship between aging, drug use, and future treatment needs.…”
mentioning
confidence: 99%
“…Chronic drug use may lead to an increased risk of hepatitis C-induced liver disease, hypertension, cardiovascular disease, mental health problems, bacterial infections, and trauma. [22][23][24][25] Substance abuse and psychiatric disorders frequently coexist; in a sample of 2864 HIV-infected adults receiving care in the United States, 47.9% screened positive for a psychiatric disorder, including major depression, dysthymia, generalized anxiety disorders, and panic attacks. 26 Illicit drug use and heavy alcohol use were independently associated with screening positive for a psychiatric disorder.…”
Section: Substance Abuse and Psychiatric Illnessmentioning
confidence: 99%
“…So kommt es, dass ä ltere Drogenabh ä ngige sowohl von den j ü ngeren Drogenabh ä ngigen ausgegrenzt werden als auch von der Durchschnittsbev ö lkerung, den Anderen. Anderson & Levy [24] haben diesen Prozess anhand qualitativer Interviews mit ä lteren Drogenabh ä ngigen in Chicago nachgezeichnet. Sie zeigen, wie die Ä lteren von den J ü ngeren an den Rand der Gruppen gedr ä ngt werden, wo sie eine Art Schattendasein f ü hren.…”
Section: Lebenslagen Und Gesundheit ä Lterer Drogenabh ä Ngiger: Ein unclassified
“…Es sind nicht mehr die Jungen, die den typischen Drogentod sterben, sondern die Ä lteren und Alten [73,75] . Das spricht daf ü r, dass sich mit zunehmendem Alter Hoff nungslosigkeit unter den Drogenabh ä ngigen breit macht [24,76] , was manche dazu veranlasst, sich ganz bewusst den sogenannten " goldenen Schuss " zu setzen.…”
Section: Lebenslagen Und Gesundheit ä Lterer Drogenabh ä Ngiger: Ein unclassified